Traumatic brain injury related paediatric mortality and morbidity in low- and middle-income countries: a systematic review - Bandyopadhyay, S; Kawka, M; Marks, K; Richards, GC; Taylor, EH; Sravanam, S; Petrinic, T; Thango, N; Figaji, A; Peter, N; Lakhoo, K (Elsevier, 2021)
Background The burden of paediatric traumatic brain injury (pTBI) in low-and-middle-income countries (LMICs) is unknown. To fill this gap, we conducted a review that aimed to characterise the causes of pTBI in LMICs, and their reported associated mortality and morbidity.